La Eslavística literaria y Centroeuropa - Pospišil, Ivo (Eslavística Complutense, 2003)
The author of the present study analyses the problems of Slavonic studies in general and of Russian studies in particular from various points of view. At the very beginning the conditions of the development of Slavonic studies linked with the impact of social sciences on their methodology and on the inner structure of philologies are stressed. In this sense the context of Central Europe, the revival of sociology and sociological approaches and the connection with Slavonic and comparative studies are accentuated.
Keywords: Slavonic and Russian; Comparative studies; Central European context